HUBUNGAN USIA MENARCHE DENGAN KEJADIAN DISMENOREA PRIMER PADA REMAJA KELAS 3 SMP DI SMPN 2 JEMBER - Zidny Nuris Yuhbaba (Jurnal Kesehatan dr. Soebandi, 2014)
Puberty is a transition period between childhood and adulthood, where there is an acceleration of growth, secondary sex characteristics arise, fertility is achieved and psychological changes occur. The design of this study uses researchers to use the correlation analysis method, namely analyzing the relationship between the age of menarche and primary dysmenorrhoea. In this study using a case control approach where researchers measure the dependent variable first, while the independent variable is traced retrospectively to determine whether there are no factors (independent variables) that play a role. Data taken together (Nursalam, 2003: 86). The population in this study is 84 young women who have experienced menarche, especially in the third grade of junior high school in SMP N 2 Jember. In this study, the used is the Purposive Sample. by collecting data using a questionnaire, the time of research data collection was May 29 to June 1 2012. The relationship between age of menarche and the incidence of primary dysmenorrhoea in adolescents was obtained 2 counts of 1.16 and 2tabs with a 5% signification of 5.99, so 2counts <2table. However, because the distribution of the signal frequency does not meet the requirement of <2 cells (33.3%), it has an expectation frequency of <5 then using the Lambda correlation. Obtained an L_b value of zero it can be concluded that there is no relationship between the age of menarche and the incidence of primary dysmenorrhoea in adolescents.